Porous polymers based on aryleneethynylene building blocks - Bunz, Uwe H. F.; Seehafer, Kai; Geyer, Florian Ludwig; Bender, Markus; Braun, Ingo; Smarsly, Emanuel; Freudenberg, Jan (Macromolecular rapid communications, 2014)
Porous conjugated polymers are synthesized by metal-catalyzed coupling reactions. The progress for porous polymers when planar or tetrahedral building blocks are connected by alkyne units into novel materials is highlighted. The most prominent reaction for the buildup of the microporous alkyne-bridged polymers is the Sonogashira reaction, connecting alkynes to aromatic iodides or bromides. The availability of the building blocks and the potency of the Sonogashira reaction allow preparing a large variety of intrinsically porous polymeric materials, in which rigid struts connect multipronged centers. The microporous polymers are used as catalysts and as storage materials for gases and sensors. Postfunctionalization schemes, understanding of structure-property relationships, and the quest for high porosity are pertinent.